Defining the subset of the patients in whom “Less is More” for hormone receptor-positive breast cancer: clinical risk vs. genomics risk - Park, Yeon Hee (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Omitting adjuvant chemotherapy by risk assessments using clinical and genomic signature is a very important topic for patients and clinician because chemotherapy has potentials to be harmful with various reasons. Currently, NCCN recommend to consider 21-gene RT-PCR assay (1) for patients with hormone receptor-positive breast cancer who have tumor beyond 0.5 cm after curative surgery (2). However, this clinical application of multi-gene assay is not enough to be useful with category 2A level of evidence. In addition, high price of the test is preventing it from becoming widely available.